Defective Treg generation and increased type 3 immune response in leukocyte adhesion deficiency 1 - ÖZEN, AHMET OĞUZHAN (My University, 2023)
In 15 Turkish LAD-1 patients and controls, we assessed the impact of pathogenic ITGB2 mutations on Th17/Treg differentiation and functions, and innate lymphoid cell (ILC) subsets. The percentage of peripheral blood Treg cells, in vitro-generated induced Tregs differentiated from naive CD4+ T cells were decreased despite the elevated absolute counts of CD4+ cells in LAD-1 patients. Serum IL-23 levels were elevated in LAD-1 patients. Post-curdlan stimulation, LAD-1 patient-derived PBMCs produced more IL-17A. Additionally, the percentages of CD18-deficient Th17 cells expanded from total or naïve CD4+ T cells were higher. The blood ILC3 subset was significantly elevated in LAD-1. Finally, LAD-1 PBMCs showed defects in trans-well migration and proliferation and were more resistant to apoptosis. Defects in de novo generation of Tregs from CD18-deficient naïve T cells and elevated Th17s, and ILC3s in LAD-1 patients\" peripheral blood suggest a type 3-skewed immunity and may contribute to LAD-1-associated autoimmune symptoms.
Keywords: Tıp; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; İmmünoloji; ALERJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; IMMUNOLOGY; ALLERGY; İmmünoloji ve Alerji; Immunology and Allergy; Immunology; ILC; LAD-1; Leukocyte adhesion deficiency; Th17; Treg